Digital Payment Revolution and the Velocity of Money: Does the Classic Inflation Model Still Hold? - Boediono, Philipo (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2026)
The unprecedented proliferation of electronic money (e-money) in Indonesia has fundamentally altered the transactional landscape, raising a critical yet underexplored question: has the digital payment revolution destabilized the classic relationship between money velocity and inflation? This study investigates the long-run and short-run dynamics between e-money transaction volume, inflation, and the velocity of money in Indonesia over the period 2011-2023, employing the Autoregressive Distributed Lag (ARDL) bounds testing approach. Annual data on nominal GDP, M2 money supply, e-money transaction values, and consumer price inflation were sourced from Bank Indonesia and the Indonesian Central Bureau of Statistics (BPS). Augmented Dickey-Fuller (ADF) unit root tests confirm that all variables are integrated of order one, I(1), making the ARDL framework appropriate. The Bounds F-test yields a statistic of 15.343, decisively exceeding the 1% critical upper bound, confirming a stable long-run cointegrating relationship. Results reveal a significant positive short-run effect of e-money on velocity but a negative long-run multiplier, suggesting that the rapid expansion of the digital monetary base ultimately depresses velocity, a phenomenon we term the “digital shadow of money.” Inflation exhibits a statistically insignificant role in both the short and long run, challenging the applicability of the classical quantity theory of money in Indonesia's digitizing economy. The CUSUM stability test confirms structural stability. These findings carry substantial implications for monetary policy design, particularly regarding the adequacy of conventional money supply targeting in an era of digital financial transformation.